Preparation method of recycled aggregate pervious concrete
By using recycled aggregate and high proportion of slag powder to replace cement in permeable concrete, combined with specific treatment steps, traditional permeable concrete is solved to find that it is difficult for traditional permeable concrete to meet the requirements of sponge urban pavement structure and long-term blockage problems, and green permeable concrete materials with high strength, high permeability and long life are achieved.
Patent Information
- Application Number
- CN202411833389.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
Traditional permeable concrete is difficult to meet the requirements of sponge urban pavement structures for porosity and bending strength, and it is prone to pore blockage and degradation of water permeability after long-term service.
Recycled aggregates are used to replace natural coarse aggregates, and a large proportion of slag powder is used to replace cement as cementitious material. The microstructure of permeable concrete is optimized through specific treatment steps such as water washing and drying, alkali trigger reaction, soaking of magnesium alginate aqueous solution and carbon dioxide gas carbonization, etc.
A fully waste aggregate green permeable concrete material with high strength and high permeability was prepared, which significantly improved the anti-blocking ability and service life of permeable concrete, while achieving resource recycling and environmental benefits.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permeable concrete, and in particular to a method for preparing recycled aggregate permeable concrete. Background Art
[0002] Permeable pavement is mainly made of permeable concrete. Its special structure not only has good air permeability and water permeability, but also has good ecological and environmental benefits such as cooling, noise reduction, and environmental improvement. In recent years, permeable concrete has begun to be widely used in road projects, effectively alleviating flood and runoff problems in densely populated areas. However, traditional permeable pavement is difficult to simultaneously meet the requirements of sponge city pavement structure for its porosity and bending strength, and is prone to pore blockage, reduced permeability, or even complete loss after long-term service.
[0003] At the same time, with the continuous advancement of urbanization and industrialization, the amount of construction solid waste and industrial solid waste has increased year by year. Due to the development of society, the needs of urban construction and environmental improvement, green and low-carbon has become the development direction of the construction field. The low-carbon economy based on low energy consumption, low pollution, low emissions and high performance, high efficiency and high benefits is a new economic development model for the concrete industry. The building materials industry has great potential to consume industrial solid waste and construction solid waste at the same time. The use of industrial solid waste such as industrial waste slag to prepare alkali-activated cementitious materials can replace cement, effectively reduce cement consumption and reduce carbon emissions. At the same time, the use of recycled coarse aggregate in construction waste as raw materials to develop recycled concrete products based on alkali-activated cementitious materials is conducive to resource reuse, energy conservation, environmental protection and sustainable development. Summary of the invention
[0004] The problem to be solved by the present invention is to provide a method for preparing recycled aggregate permeable concrete in view of the above-mentioned deficiencies in the prior art. The method proposes a method for preparing permeable concrete by using recycled aggregate to completely replace natural coarse aggregate, and using a large proportion (30%) of slag powder to replace cement as a cementitious material, so as to prepare a high-strength and high-permeability green permeable concrete material made of all-waste aggregate.
[0005] The above-mentioned object of the present invention is achieved through the following technical solutions: A method for preparing recycled aggregate permeable concrete comprises the following steps: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2: washing and drying the waste stone powder obtained in S1, adding glass powder and sodium hydroxide to react to obtain a sodium silicate alkali activator; S3: firstly add the coarse aggregate obtained in S1 into the magnesium alginate aqueous solution and soak it until it is saturated with water, and then sequentially add sodium polyacrylate, mango fat and hydrogenated polyisobutylene, stir and mix, and then introduce carbon dioxide gas for carbonization. After the carbonization is completed, it is post-processed to obtain recycled aggregate; S4 mixes cement, slag powder, the alkali activator obtained in S2, machine-made sand, the recycled aggregate obtained in S3, a polycarboxylate water-reducing agent and water to obtain permeable concrete.
[0006] The key technical problems that the present invention intends to solve are: 1. Due to the differences in structure and composition between permeable concrete and ordinary concrete, their preparation and design processes are also very different; for permeable concrete, since it needs to meet the permeability requirements, its porosity must be maintained within a certain range, and its strength and structural stability must also be guaranteed; therefore, it is difficult for traditional permeable pavement to simultaneously meet the requirements of sponge city pavement structure for its porosity and flexural strength; combining the material properties of different solid waste aggregates, improving the microstructure inside the concrete by adjusting the slag replacement rate in the concrete, and breaking through the technical bottleneck that high permeability and high strength of traditional permeable concrete cannot coexist is one of the key technical problems to be solved by the present invention; 2. The clogging effect is considered to be the main cause of the failure of permeable pavement. The clogging effect reduces the effective service life of permeable pavement and hinders the widespread application of permeable concrete pavement. Existing permeable pavements are prone to pore blockage, reduced permeability or even complete loss after long-term service. Since the clogging and penetration mechanisms inside the permeable pavement structure are still unclear at this stage, there is a lack of evaluation, prediction and early warning theories for the operation effect of permeable pavement. Determining the permeability coefficient of permeable pavement to quantitatively reflect its degree of clogging, and exploring the content of retained particles inside the permeable concrete and its vertical distribution law are the second key technical problems that the present invention intends to solve.
[0007] Therefore, the present invention adopts experimental research, theoretical analysis and numerical simulation methods to carry out systematic research on the research and development, structural design and long-term service performance of new permeable green permeable paving materials; the specific research contents are as follows: 1. Preparation technology of new materials for all-solid waste aggregate permeable paving: Based on the physical and chemical properties of recycled aggregates made from crushed solid waste, the research and analysis were carried out, and the abandoned construction waste was crushed into different particle sizes and used as coarse aggregate to prepare permeable concrete; natural crushed stone was used as the control group to study the influence of aggregate type and particle size on the performance of permeable concrete; by adding slag as an auxiliary cementitious material to replace cement, the structure and construction of permeable concrete were improved, and the empirical relationship between permeability coefficient and porosity was analyzed to improve the structure and construction mechanism of permeable concrete, and the influence of the amount of auxiliary cementitious materials on the structure and performance of the sample was studied; through the orthogonal test method, the design idea of "target porosity design-paste water-cement ratio design-aggregate particle size design" was proposed, and high-strength and high-permeability environmentally friendly permeable concrete was prepared based on the synergistic effect of multiple solid wastes; 2. Design method of permeable pavement structure system: Analyze the basic assumptions of the pavement and the requirements of each structural layer of the pavement, select the appropriate model size according to the actual pavement working conditions, establish the solid waste aggregate permeable concrete pavement structure model through ABAQUS, set appropriate boundary conditions and reasonable grid division; carry out the analysis of the influencing factors of load stress, consider the influence of various comprehensive factors such as soil foundation, plate thickness, plate length, modulus ratio on load stress; consider the fatigue coefficient generated by repeated vehicle loads, compare the maximum principal stress values obtained by ABAQUS under various variables, refer to the specifications and relevant literature to obtain the correction coefficient, and correct the actual maximum principal stress; carry out the analysis of the influencing factors of temperature stress, consider the influence of temperature gradient, plate thickness, plate length and other factors on temperature stress; consider the fatigue coefficient generated by repeated temperature loads, compare the maximum principal stress values obtained by ABAQUS under various variables, refer to the specifications and relevant literature to obtain the correction coefficient, and correct the actual temperature stress; based on the calculation of the above correction parameters, propose a design method for permeable pavement structure with solid waste aggregate; 3. Long-term performance evaluation model of permeable pavement structure: Based on the orthogonal factor table, different graded blocking materials are selected to cross-compare the influence of three factors, namely head height, gravel grading and surface torrent, on the permeability and resistivity of permeable concrete, revealing the microscopic mechanism of permeable concrete particles blocking pores under rainwater seepage under different conditions; a permeable pavement blocking test is carried out on the engineering site simulating the full life cycle of the permeable pavement, and combined with the three-dimensional numerical model of fluid-solid coupling in the permeable pavement, the mechanical characteristics of the interaction between the seepage field in the pores and the blocking particles, as well as the influence mechanism of water infiltration on particle movement, are explored to construct a prediction model for the attenuation of the permeability function of the permeable concrete pavement.
[0008] Therefore, in order to solve the urgent problems in the application research of solid waste aggregates in permeable pavement, a multi-level research method combining experimental research, theoretical analysis, numerical simulation and engineering application can be adopted to carry out systematic research on key issues such as solid waste aggregate permeable pavement materials, permeable pavement structure design methods and long-term performance evaluation. Based on the theory of multi-solid waste synergy, the resource utilization of solid waste is realized, a new type of permeable pavement material made of all waste aggregates is developed, a design method for permeable pavement structure system is proposed, a prediction model for the attenuation of permeability function of permeable pavement is built, and a permeable pavement construction theory and technology system covering materials, structures and engineering levels is established.
[0009] In the process of developing a new type of permeable paving material made of all-waste aggregates and realizing resource utilization of solid wastes based on the theory of synergistic effects of multiple solid wastes, that is, by adopting the above-mentioned technical scheme, firstly, by using waste concrete as raw material, this method realizes the recycling of resources and reduces the impact of construction waste on the environment; after the waste concrete is crushed and screened, not only coarse aggregates with suitable particle sizes can be obtained, but also waste stone powder with a particle size of less than 0.075 mm can be obtained. After washing, drying and chemical reaction, these stone powders are converted into sodium silicate alkali activators, which further improves the utilization rate of materials; secondly, the method uses magnesium alginate to treat the coarse aggregates. The steps of soaking in aqueous solution, adding various additives for stirring and mixing, and carbonization with carbon dioxide gas can not only optimize the cross-sectional bonding between the recycled aggregate and the cement paste, and enhance the strength and durability of the recycled aggregate, but also introduce a microporous structure through the carbonization process, so that the finally prepared permeable concrete has good permeability; finally, by mixing cement, slag powder, alkali activator, machine-made sand, recycled aggregate, polycarboxylic acid water reducer and water, the prepared permeable concrete not only has high strength and durability, but also has good permeability, which is conducive to the infiltration of rainwater and the replenishment of groundwater, and is of great significance to promoting the development of green building materials.
[0010] Furthermore, in the S2, the waste stone powder is first dried at 100-110°C for 12-24h, then added into water and stirred, filtered, the obtained filter residue is dried at 100-110°C for 12-24h, then glass powder and sodium hydroxide are added and stirred, and reacted at 160-170°C for 0.5-1.0h to obtain a sodium silicate alkali activator.
[0011] Furthermore, in S2, the volume ratio of the dried waste stone powder and water is controlled to be 1:5-7.
[0012] Furthermore, in S2, the mass ratio of the dried waste stone powder, glass powder and sodium hydroxide is controlled to be 1:2~5:1~3.
[0013] Compared with directly using waste stone powder, the sodium silicate alkali activator prepared from washed stone powder, glass powder and sodium hydroxide can further improve the activity of the sodium silicate alkali activator, thereby achieving a certain improvement in the mechanical properties of permeable concrete. During the reaction, this sodium silicate alkali activator can chemically react with calcium ions in the cement paste to generate hydrated calcium silicate gel with higher strength, thereby significantly improving the mechanical properties of permeable concrete.
[0014] Furthermore, in the S3, the coarse aggregate is first added to the magnesium alginate aqueous solution and soaked for 10-12 hours until it is saturated with water. During the period, the mixture is stirred for 4-6 times at equal time intervals, each time at a speed of 800-1200 r / min for 20-30 minutes, and sodium polyacrylate, mango fat and hydrogenated polyisobutylene are added before the 2nd to 4th stirring, respectively, and then the mixture is continuously stirred, and carbon dioxide gas with a flow rate of 1.0-3.0 L / min and a volume concentration of 50-99% is introduced, and the mixture is carbonized at 40-60° C. for 20-40 minutes, filtered, and the obtained filter residue is dried at 100-110° C. for 12-24 hours to obtain recycled aggregate.
[0015] Furthermore, in S3, the volume ratio of the coarse aggregate to the magnesium alginate aqueous solution is controlled to be 1:4-6.
[0016] Furthermore, in S3, the mass concentration of the magnesium alginate aqueous solution is 0.5-1.0%.
[0017] Furthermore, in S3, the mass ratio of coarse aggregate, sodium polyacrylate, mango fat and hydrogenated polyisobutylene is controlled to be 1:0.2~0.8:0.1~0.2:0.4~0.8.
[0018] After the magnesium alginate aqueous solution is mixed with the coarse aggregate, the soaking time is controlled to be 24 to 48 hours to ensure that the magnesium alginate can fully penetrate into the micropores of the aggregate. Subsequently, additives are added for stirring and mixing, and the additives include but are not limited to water reducers, early strength agents and antifreeze agents to improve the workability and early strength of the concrete. Next, the mixture is carbonized with carbon dioxide gas, and the carbonization time is controlled to be 1 to 3 hours to form a microporous structure and enhance the water permeability.
[0019] Furthermore, in S4, machine-made sand, recycled aggregate and half of the water are first added to a mixer and mixed for 30 seconds, then cement, slag powder and alkali activator are added and mixed for 15 seconds, and then polycarboxylate water reducer and the remaining water are added and mixed for 90 seconds to obtain permeable concrete.
[0020] Furthermore, in S4, the permeable concrete includes 378 kg / m³ of cement, 162 kg / m³ of slag powder, 16 kg / m³ of alkali activator, 698 kg / m³ of machine-made sand, 703 kg / m³ of recycled aggregate with a particle size of 5-10 mm, 301 kg / m³ of recycled aggregate with a particle size of 10-20 mm, 12 kg / m³ of polycarboxylate water reducer, and the balance is water.
[0021] Cement, slag powder, alkali activator, machine-made sand, recycled aggregate, polycarboxylate water reducer and water are mixed in a certain proportion, stirred evenly and cast into shape. The formed concrete is cured for 28 days under standard curing conditions to ensure that its strength and durability meet the design requirements. The permeable concrete finally prepared has high strength and durability, while maintaining good permeability, which can effectively promote rainwater infiltration and groundwater replenishment.
[0022] In summary, the beneficial technical effects of the present invention are: 1. Through the preparation method of the present invention, permeable concrete that meets the requirements of sponge city pavement structure can be prepared, and its porosity, flexural strength and structural stability all meet the design standards, effectively solving the technical bottleneck that high permeability and high strength of traditional permeable concrete cannot coexist; 2. The present invention significantly improves the anti-clogging ability of permeable concrete by optimizing the material composition and structural design of permeable pavement, prolongs the effective service life of permeable pavement, reduces the problem of water permeability degradation caused by clogging effect, and provides technical guarantee for the widespread application of permeable concrete pavement; 3. The present invention makes full use of waste concrete, such as recycled aggregate, waste stone powder, etc. in material selection, which not only improves the performance of permeable concrete, but also promotes the resource utilization of solid waste, and has significant environmental and social benefits. DETAILED DESCRIPTION
[0023] In order to make the technical means, creative features, objectives and functions of the present invention clearer and easier to understand, the present invention is further described below in conjunction with specific implementation methods; Embodiment 1: A method for preparing recycled aggregate permeable concrete disclosed in the present invention comprises the following steps: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2 washes and dries the waste stone powder obtained in S1, and then adds glass powder and sodium hydroxide to react to obtain a sodium silicate alkali activator; S3: firstly add the coarse aggregate obtained in S1 into the magnesium alginate aqueous solution and soak it until it is saturated with water, and then sequentially add sodium polyacrylate, mango fat and hydrogenated polyisobutylene, stir and mix, and then introduce carbon dioxide gas for carbonization. After the carbonization is completed, it is post-processed to obtain recycled aggregate; S4 mixes cement, slag powder, the alkali activator obtained in S2, machine-made sand, the recycled aggregate obtained in S3, a polycarboxylate water-reducing agent and water to obtain permeable concrete; wherein, The cement is P.Ⅱ52.5 silicate cement; The slag powder is S95 grade slag powder, with density ≥2.8g / cm³, specific surface area ≥400㎡ / kg, fluidity ratio ≥95%, loss on ignition ≤1.0%, 7-day activity index ≥70%, 28-day activity index ≥95% The machine-made sand is medium sand of Class II in Zone 2; The admixture is polycarboxylic acid high-performance water-reducing agent, with a pH value of 4.0~4.7, a density of 1.02~1.06g / cm³, a cement paste fluidity of ≥180mm, a water reduction rate of ≥25%, an air content of ≤6.0%, a 1h slump loss over time of ≤80mm, a 7-day compressive strength ratio of ≥150%, and a 28-day compressive strength ratio of ≥140%.
[0024] Embodiment 2: A method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Embodiment 1 in that it comprises the following steps: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2 firstly dries the waste stone powder at 105°C for 20h, then adds it into water and stirs it, controls the volume ratio of the waste stone powder and water after drying to be 1:6, filters it, dries the filter residue at 105°C for 20h, then adds glass powder and sodium hydroxide and stirs it, controls the mass ratio of the waste stone powder, glass powder and sodium hydroxide after drying to be 1:3:2, and reacts it at 165°C for 40min to obtain a sodium silicate alkali activator; S3: first add coarse aggregate into magnesium alginate aqueous solution, control the volume ratio of coarse aggregate and magnesium alginate aqueous solution to be 1:5, the mass concentration of magnesium alginate aqueous solution to be 0.8%, soak for 10 hours until saturated with water, stir 5 times at equal time intervals, stir for 15 minutes each time at a speed of 1000r / min, and add sodium polyacrylate, mango fat and hydrogenated polyisobutylene respectively before the 2nd to 4th stirring, control the mass ratio of coarse aggregate, sodium polyacrylate, mango fat and hydrogenated polyisobutylene to be 1:0.6:0.1:0.5, then continue stirring, and introduce carbon dioxide gas with a flow rate of 1.2L / min and a volume concentration of 85%, carbonize at 50℃ for 30min, filter, and dry the obtained filter residue at 105℃ for 20h to obtain recycled aggregate; S4 prepares raw materials for permeable concrete, which include 378kg / m³ of cement, 162kg / m³ of slag powder, 16kg / m³ of alkali activator, 698kg / m³ of machine-made sand, 703kg / m³ of recycled aggregate with a particle size of 5-10mm, 301kg / m³ of recycled aggregate with a particle size of 10-20mm, 12kg / m³ of polycarboxylate water reducer, and the balance is water; first, add the machine-made sand, recycled aggregate and half of the water into a mixer and mix for 30s, then add cement, slag powder and alkali activator and mix for 15s, then add the polycarboxylate water reducer and the remaining water and mix for 90s to obtain permeable concrete.
[0025] Concrete mechanical tests were carried out according to GB / T50081-2002 standard test method for mechanical properties of ordinary concrete; the water permeability coefficient was measured using TSXS-1 concrete water permeability coefficient tester; the continuous porosity was measured using a mercury intrusion meter; the compressive strength loss rate after freeze-thaw cycles was measured according to GB / T50082-2009 standard test method for long-term properties and durability of ordinary concrete.
[0026] After testing, the 28d compressive strength of the permeable concrete prepared in Example 2 was 102.8 MPa, the water permeability (25°C) was 9.1 mm / s, the continuous porosity was 28.9%, and the compressive strength loss rate after 25 freeze-thaw cycles was 3.17%.
[0027] Embodiment 3: A method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Embodiment 1 in that it comprises the following steps: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2 firstly dries the waste stone powder at 105°C for 20h, then adds it into water and stirs it, controls the volume ratio of the waste stone powder and water after drying to be 1:5, filters it, dries the filter residue at 105°C for 20h, then adds glass powder and sodium hydroxide and stirs it, controls the mass ratio of the waste stone powder, glass powder and sodium hydroxide after drying to be 1:2:1, and reacts it at 165°C for 40min to obtain a sodium silicate alkali activator; S3: first add coarse aggregate into magnesium alginate aqueous solution, control the volume ratio of coarse aggregate and magnesium alginate aqueous solution to be 1:4, the mass concentration of magnesium alginate aqueous solution to be 0.5%, soak for 10 hours until saturated with water, stir 5 times at equal time intervals, stir for 15 minutes each time at a speed of 1000r / min, and add sodium polyacrylate, mango fat and hydrogenated polyisobutylene respectively before the 2nd to 4th stirring, control the mass ratio of coarse aggregate, sodium polyacrylate, mango fat and hydrogenated polyisobutylene to be 1:0.2:0.2:0.4, then continue stirring, and introduce carbon dioxide gas with a flow rate of 1.0L / min and a volume concentration of 50%, carbonize at 50℃ for 30min, filter, and dry the obtained filter residue at 105℃ for 20h to obtain recycled aggregate; S4 prepares raw materials for permeable concrete, which include 378kg / m³ of cement, 162kg / m³ of slag powder, 16kg / m³ of alkali activator, 698kg / m³ of machine-made sand, 703kg / m³ of recycled aggregate with a particle size of 5-10mm, 301kg / m³ of recycled aggregate with a particle size of 10-20mm, 12kg / m³ of polycarboxylate water reducer, and the balance is water; first, add the machine-made sand, recycled aggregate and half of the water into a mixer and mix for 30s, then add cement, slag powder and alkali activator and mix for 15s, then add the polycarboxylate water reducer and the remaining water and mix for 90s to obtain permeable concrete.
[0028] After testing, the permeable concrete prepared in Example 3 has a 28d compressive strength of 99.6 MPa, a water permeability coefficient (25°C) of 8.8 mm / s, a continuous porosity of 26.6%, and a compressive strength loss rate of 3.25% after 25 freeze-thaw cycles.
[0029] Embodiment 4 is a method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Embodiment 1 in that it comprises the following steps: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2 firstly dries the waste stone powder at 105°C for 20h, then adds it into water and stirs it, controls the volume ratio of the waste stone powder and water after drying to be 1:5, filters it, dries the filter residue at 105°C for 20h, then adds glass powder and sodium hydroxide and stirs it, controls the mass ratio of the waste stone powder, glass powder and sodium hydroxide after drying to be 1:3:1, and reacts it at 165°C for 40min to obtain a sodium silicate alkali activator; S3: first add coarse aggregate into magnesium alginate aqueous solution, control the volume ratio of coarse aggregate and magnesium alginate aqueous solution to be 1:4, the mass concentration of magnesium alginate aqueous solution to be 0.6%, soak for 10 hours until water absorption saturation, stir 5 times at equal time intervals, stir for 15 minutes each time at a speed of 1000r / min, and add sodium polyacrylate, mango fat and hydrogenated polyisobutylene respectively before the 2nd to 4th stirring, control the mass ratio of coarse aggregate, sodium polyacrylate, mango fat and hydrogenated polyisobutylene to be 1:0.4:0.1:0.4, then continue stirring, and introduce carbon dioxide gas with a flow rate of 2.0L / min and a volume concentration of 60%, carbonize at 50℃ for 30min, filter, and dry the obtained filter residue at 105℃ for 20h to obtain recycled aggregate; S4 prepares raw materials for permeable concrete, which include 378kg / m³ of cement, 162kg / m³ of slag powder, 16kg / m³ of alkali activator, 698kg / m³ of machine-made sand, 703kg / m³ of recycled aggregate with a particle size of 5-10mm, 301kg / m³ of recycled aggregate with a particle size of 10-20mm, 12kg / m³ of polycarboxylate water reducer, and the balance is water; first, add the machine-made sand, recycled aggregate and half of the water into a mixer and mix for 30s, then add cement, slag powder and alkali activator and mix for 15s, then add the polycarboxylate water reducer and the remaining water and mix for 90s to obtain permeable concrete.
[0030] After testing, the 28d compressive strength of the permeable concrete prepared in Example 4 was 100.5 MPa, the water permeability (25°C) was 9.5 mm / s, the continuous porosity was 27.9%, and the compressive strength loss rate after 25 freeze-thaw cycles was 3.88%.
[0031] Embodiment 5: A method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Embodiment 1 in that it comprises the following steps: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2 firstly dries the waste stone powder at 105°C for 20 hours, then adds it into water and stirs and mixes it, controls the volume ratio of the waste stone powder after drying to water to be 1:7, filters it, dries the filter residue at 105°C for 20 hours, then adds glass powder and sodium hydroxide and stirs and mixes it, controls the mass ratio of the waste stone powder, glass powder and sodium hydroxide after drying to be 1:4:3, and reacts it at 165°C for 40 minutes to obtain a sodium silicate alkali activator; S3: first add coarse aggregate into magnesium alginate aqueous solution, control the volume ratio of coarse aggregate and magnesium alginate aqueous solution to be 1:6, the mass concentration of magnesium alginate aqueous solution to be 0.7%, soak for 10 hours until saturated with water, stir 5 times at equal time intervals, stir for 15 minutes each time at a speed of 1000r / min, and add sodium polyacrylate, mango fat and hydrogenated polyisobutylene respectively before the 2nd to 4th stirring, control the mass ratio of coarse aggregate, sodium polyacrylate, mango fat and hydrogenated polyisobutylene to be 1:0.6:0.2:0.6, then continue stirring, and introduce carbon dioxide gas with a flow rate of 2.5L / min and a volume concentration of 70%, carbonize at 50℃ for 30min, filter, and dry the obtained filter residue at 105℃ for 20h to obtain recycled aggregate; S4 prepares raw materials for permeable concrete, which include 378kg / m³ of cement, 162kg / m³ of slag powder, 16kg / m³ of alkali activator, 698kg / m³ of machine-made sand, 703kg / m³ of recycled aggregate with a particle size of 5-10mm, 301kg / m³ of recycled aggregate with a particle size of 10-20mm, 12kg / m³ of polycarboxylate water reducer, and the balance is water; first, add the machine-made sand, recycled aggregate and half of the water into a mixer and mix for 30s, then add cement, slag powder and alkali activator and mix for 15s, then add the polycarboxylate water reducer and the remaining water and mix for 90s to obtain permeable concrete.
[0032] After testing, the permeable concrete prepared in Example 5 has a 28d compressive strength of 98.7 MPa, a water permeability coefficient (25°C) of 10.1 mm / s, a continuous porosity of 26.3%, and a compressive strength loss rate of 3.85% after 25 freeze-thaw cycles.
[0033] Embodiment 6: A method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Embodiment 1 in that it comprises the following steps: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2 firstly dries the waste stone powder at 105°C for 20h, then adds it into water and stirs it, controls the volume ratio of the waste stone powder and water after drying to be 1:7, filters it, dries the filter residue at 105°C for 20h, then adds glass powder and sodium hydroxide and stirs it, controls the mass ratio of the waste stone powder, glass powder and sodium hydroxide after drying to be 1:5:3, and reacts it at 165°C for 40min to obtain a sodium silicate alkali activator; S3: first add coarse aggregate into magnesium alginate aqueous solution, control the volume ratio of coarse aggregate and magnesium alginate aqueous solution to be 1:6, the mass concentration of magnesium alginate aqueous solution to be 1.0%, soak for 10 hours until saturated with water, stir 5 times at equal time intervals, stir for 15 minutes each time at a speed of 1000r / min, and add sodium polyacrylate, mango fat and hydrogenated polyisobutylene respectively before the 2nd to 4th stirring, control the mass ratio of coarse aggregate, sodium polyacrylate, mango fat and hydrogenated polyisobutylene to be 1:0.8:0.2:0.8, then continue stirring, and introduce carbon dioxide gas with a flow rate of 3.0L / min and a volume concentration of 99%, carbonize at 50℃ for 30min, filter, and dry the obtained filter residue at 105℃ for 20h to obtain recycled aggregate; S4 prepares raw materials for permeable concrete, which include 378kg / m³ of cement, 162kg / m³ of slag powder, 16kg / m³ of alkali activator, 698kg / m³ of machine-made sand, 703kg / m³ of recycled aggregate with a particle size of 5-10mm, 301kg / m³ of recycled aggregate with a particle size of 10-20mm, 12kg / m³ of polycarboxylate water reducer, and the balance is water; first, add the machine-made sand, recycled aggregate and half of the water into a mixer and mix for 30s, then add cement, slag powder and alkali activator and mix for 15s, then add the polycarboxylate water reducer and the remaining water and mix for 90s to obtain permeable concrete.
[0034] After testing, the permeable concrete prepared in Example 6 has a 28d compressive strength of 99.2 MPa, a water permeability coefficient (25°C) of 10.5 mm / s, a continuous porosity of 28.4%, and a compressive strength loss rate of 3.79% after 25 freeze-thaw cycles.
[0035] Embodiment 7: A method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Embodiment 1 in that it comprises the following steps: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2 firstly dries the waste stone powder at 100°C for 12 hours, then adds it into water and stirs it, controls the volume ratio of the dried waste stone powder to water to be 1:6, filters it, dries the obtained filter residue at 100°C for 12 hours, then adds glass powder and sodium hydroxide and stirs it, controls the mass ratio of the dried waste stone powder, glass powder and sodium hydroxide to be 1:3:2, and reacts it at 160°C for 30 minutes to obtain a sodium silicate alkali activator; S3: first add coarse aggregate into magnesium alginate aqueous solution, control the volume ratio of coarse aggregate and magnesium alginate aqueous solution to be 1:5, the mass concentration of magnesium alginate aqueous solution to be 0.8%, soak for 11 hours until saturated with water, stir 5 times at equal time intervals, stir for 20 minutes each time at a speed of 800r / min, and add sodium polyacrylate, mango fat and hydrogenated polyisobutylene respectively before the 2nd to 4th stirring, control the mass ratio of coarse aggregate, sodium polyacrylate, mango fat and hydrogenated polyisobutylene to be 1:0.6:0.1:0.5, then continue stirring, and introduce carbon dioxide gas with a flow rate of 1.2L / min and a volume concentration of 85%, carbonize at 40℃ for 20min, filter, and dry the obtained filter residue at 100℃ for 12h to obtain recycled aggregate; S4 prepares raw materials for permeable concrete, which include 378kg / m³ of cement, 162kg / m³ of slag powder, 16kg / m³ of alkali activator, 698kg / m³ of machine-made sand, 703kg / m³ of recycled aggregate with a particle size of 5-10mm, 301kg / m³ of recycled aggregate with a particle size of 10-20mm, 12kg / m³ of polycarboxylate water reducer, and the balance is water; first, add the machine-made sand, recycled aggregate and half of the water into a mixer and mix for 30s, then add cement, slag powder and alkali activator and mix for 15s, then add the polycarboxylate water reducer and the remaining water and mix for 90s to obtain permeable concrete.
[0036] After testing, the permeable concrete prepared in Example 7 has a 28d compressive strength of 98.2 MPa, a water permeability coefficient (25°C) of 8.5 mm / s, a continuous porosity of 27.3%, and a compressive strength loss rate of 3.64% after 25 freeze-thaw cycles.
[0037] Embodiment 8: A method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Embodiment 1 in that it comprises the following steps: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2 firstly dries the waste stone powder at 110°C for 24 hours, then adds it into water and stirs and mixes it, controls the volume ratio of the waste stone powder and water after drying to be 1:6, filters it, dries the filter residue at 110°C for 24 hours, then adds glass powder and sodium hydroxide and stirs and mixes it, controls the mass ratio of the waste stone powder, glass powder and sodium hydroxide after drying to be 1:3:2, and reacts it at 170°C for 60 minutes to obtain a sodium silicate alkali activator; S3: first add coarse aggregate into magnesium alginate aqueous solution, control the volume ratio of coarse aggregate and magnesium alginate aqueous solution to be 1:5, the mass concentration of magnesium alginate aqueous solution to be 0.8%, soak for 12 hours until saturated with water, stir 5 times at equal time intervals, stir for 30 minutes each time at a speed of 1200r / min, and add sodium polyacrylate, mango fat and hydrogenated polyisobutylene respectively before the 2nd to 4th stirring, control the mass ratio of coarse aggregate, sodium polyacrylate, mango fat and hydrogenated polyisobutylene to be 1:0.6:0.1:0.5, then continue stirring, and introduce carbon dioxide gas with a flow rate of 1.2L / min and a volume concentration of 85%, carbonize at 60℃ for 40min, filter, and dry the obtained filter residue at 110℃ for 24h to obtain recycled aggregate; S4 prepares raw materials for permeable concrete, which include 378kg / m³ of cement, 162kg / m³ of slag powder, 16kg / m³ of alkali activator, 698kg / m³ of machine-made sand, 703kg / m³ of recycled aggregate with a particle size of 5-10mm, 301kg / m³ of recycled aggregate with a particle size of 10-20mm, 12kg / m³ of polycarboxylate water reducer, and the balance is water; first, add the machine-made sand, recycled aggregate and half of the water into a mixer and mix for 30s, then add cement, slag powder and alkali activator and mix for 15s, then add the polycarboxylate water reducer and the remaining water and mix for 90s to obtain permeable concrete.
[0038] After testing, the 28d compressive strength of the permeable concrete prepared in Example 8 was 98.7 MPa, the water permeability (25°C) was 9.9 mm / s, the continuous porosity was 27.8%, and the compressive strength loss rate after 25 freeze-thaw cycles was 3.09%.
[0039] Comparative Example 1 is a method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Example 1 in that, in S2, no water washing is performed.
[0040] After testing, the permeable concrete prepared in Comparative Example 1 had a 28d compressive strength of 67.2 MPa, a water permeability coefficient (25°C) of 8.1 mm / s, a continuous porosity of 24.5%, and a compressive strength loss rate of 6.88% after 25 freeze-thaw cycles.
[0041] Comparative Example 2 is a method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Example 1 in that sodium alginate is not used in S3.
[0042] After testing, the permeable concrete prepared in Comparative Example 2 had a 28d compressive strength of 76.4 MPa, a water permeability coefficient (25°C) of 7.6 mm / s, a continuous porosity of 25.3%, and a compressive strength loss rate of 9.42% after 25 freeze-thaw cycles.
[0043] Comparative Example 3 is a method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Example 1 in that sodium polyacrylate is not used in S3.
[0044] After testing, the permeable concrete prepared in Comparative Example 3 had a 28d compressive strength of 50.2 MPa, a water permeability coefficient (25°C) of 5.6 mm / s, a continuous porosity of 12.3%, and a compressive strength loss rate of 10.87% after 25 freeze-thaw cycles.
[0045] Comparative Example 4 is a method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Example 1 in that, in S3, mango butter is not used.
[0046] After testing, the permeable concrete prepared in Comparative Example 4 had a 28d compressive strength of 89.5 MPa, a water permeability coefficient (25°C) of 5.1 mm / s, a continuous porosity of 12.5%, and a compressive strength loss rate of 4.58% after 25 freeze-thaw cycles.
[0047] Comparative Example 5 is a method for preparing recycled aggregate permeable concrete disclosed in the present invention, which is different from Example 1 in that hydrogenated polyisobutylene is not used in S3.
[0048] After testing, the permeable concrete prepared in Comparative Example 5 had a 28d compressive strength of 77.2 MPa, a water permeability coefficient (25°C) of 3.9 mm / s, a continuous porosity of 14.6%, and a compressive strength loss rate of 5.99% after 25 freeze-thaw cycles.
[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing recycled aggregate permeable concrete, characterized in that: The following steps are included: S1 crushes and screens the waste concrete in sequence to obtain waste stone powder with a particle size of less than 0.075 mm and coarse aggregate with a particle size of 5 to 30 mm; S2: washing and drying the waste stone powder obtained in S1, adding glass powder and sodium hydroxide to react to obtain a sodium silicate alkali activator; S3: firstly add the coarse aggregate obtained in S1 into the magnesium alginate aqueous solution and soak it until it is saturated with water, and then sequentially add sodium polyacrylate, mango fat and hydrogenated polyisobutylene, stir and mix, and then introduce carbon dioxide gas for carbonization. After the carbonization is completed, it is post-processed to obtain recycled aggregate; S4 mixes cement, slag powder, the alkali activator obtained in S2, machine-made sand, the recycled aggregate obtained in S3, a polycarboxylate water-reducing agent and water to obtain permeable concrete.
2. The method for preparing recycled aggregate permeable concrete according to claim 1, characterized in that: In the S2, the waste stone powder is first dried at 100-110°C for 12-24h, then added into water and stirred, filtered, the obtained filter residue is dried at 100-110°C for 12-24h, then glass powder and sodium hydroxide are added, stirred, and reacted at 160-170°C for 0.5-1.0h to obtain a sodium silicate alkali activator.
3. The method for preparing a recycled aggregate permeable concrete according to claim 2, characterized in that: In S2, the volume ratio of the dried waste stone powder and water is controlled to be 1:5-7.
4. The method for preparing recycled aggregate permeable concrete according to claim 2, characterized in that: In S2, the mass ratio of the dried waste stone powder, glass powder and sodium hydroxide is controlled to be 1:2~5:1~3.
5. The method for preparing recycled aggregate permeable concrete according to claim 1, characterized in that: In the S3, the coarse aggregate is first added to the magnesium alginate aqueous solution and soaked for 10-12 hours until it is saturated with water. During the period, the mixture is stirred for 4-6 times at equal time intervals, each time at a speed of 800-1200 r / min for 20-30 minutes, and sodium polyacrylate, mango fat and hydrogenated polyisobutylene are added before the second to fourth stirrings, respectively, and then the mixture is continuously stirred, and carbon dioxide gas with a flow rate of 1.0-3.0 L / min and a volume concentration of 50-99% is introduced, and the mixture is carbonized at 40-60° C. for 20-40 minutes, filtered, and the obtained filter residue is dried at 100-110° C. for 12-24 hours to obtain recycled aggregate.
6. The method for preparing recycled aggregate permeable concrete according to claim 5, characterized in that: In S3, the volume ratio of the coarse aggregate to the magnesium alginate aqueous solution is controlled to be 1:4-6.
7. The method for preparing recycled aggregate permeable concrete according to claim 5, characterized in that: In S3, the mass concentration of the magnesium alginate aqueous solution is 0.5-1.0%.
8. The method for preparing recycled aggregate permeable concrete according to claim 5, characterized in that: In S3, the mass ratio of coarse aggregate, sodium polyacrylate, mango fat and hydrogenated polyisobutylene is controlled to be 1:0.2-0.8:0.1-0.2:0.4-0.
8.
9. The method for preparing recycled aggregate permeable concrete according to claim 1, characterized in that: In the S4, machine-made sand, recycled aggregate and half of the water are first added into a mixer and mixed for 30 seconds, then cement, slag powder and alkali activator are added and mixed for 15 seconds, and then polycarboxylate water reducer and the remaining water are added and mixed for 90 seconds to obtain permeable concrete.
10. The method for preparing recycled aggregate permeable concrete according to claim 9, characterized in that: In the S4, the permeable concrete includes 378 kg / m³ of cement, 162 kg / m³ of slag powder, 16 kg / m³ of alkali activator, 698 kg / m³ of machine-made sand, 703 kg / m³ of recycled aggregate with a particle size of 5-10 mm, 301 kg / m³ of recycled aggregate with a particle size of 10-20 mm, 12 kg / m³ of polycarboxylate water reducer, and the balance is water.
Citation Information
Cited By
Alkali-activated cementing material capable of being degraded and remolded as well as preparation method and application of alkali-activated cementing material
CN121270120A